An analysis of Chinese students' use of Chinese essay references: Another role for international students in the internationalisation of the curriculum. Issue 2 (1st June 2022) - Lim, Miguel Antonio; Huang, Zhuo Min
Abstract: Many studies have addressed the needs and challenges of international students in their host countries; however, there is relatively less work on the potential contributions these students make to their curricula. This article presents a bibliographic analysis of the academic references (n = 7, 273) used by Chinese students to construct their final essays on the theme of education and international development at a leading global university based in the United Kingdom. It examines (1) what knowledge resources are used in their essays; and (2) what the characteristics and patterns of these choices are. When allowed to construct their own essays, Chinese students appear to choose to use a significant proportion of Chinese knowledge resources within English academic essays. This use increases when their lecturers and tutors explain and accept the value of non-English academic resources. This article then discusses the implications of this result for lecturers.